Asma não controlada em crianças e adolescentes e sua relação com osdistúrbios psicoafetivos: escutando o paciente - Maria Candida Marques (2012)
The present study investigates the issue of the clinical method in contemporary medicine, its conquests and its impasses from the perspective of psychoanalytical theory. Based on cases of children and adolescents with partly controlled and uncontrolld asthma associated the psycho-affective disorders, it discusses the current biotechnological model that excludes patients subjectivity and consider possible contributions of a medical clinical practice under psychoanalytical theory orientation. Without the purpose to make a judgment on the normative medical practice or suggest a humanized clinical model , the author presents his impasses in clinical attendance of these patients while refers to his approach as a psychoanalytically oriented physician. Referring to psychoanalytical theory conceived by Freud and Lacan, this study points out that language itself, through significant chain structure, enrolls a symbolic network with constituent effects on the symptoms and psychic reality of the individual. From this statement, the author discusses possibilities of transferential handling and displacements in other discursive positions through an opening of a hearing window by the physician with potential patients symptom re-significance. While the author aims to describe the experience undergone as an psychoanalytically oriented physician, he testifies the transformations and effects of this iniative in his clinical practice, as well as in the symptomatic construction of these patients